Estimation of Epidemiological Effectiveness of the Program of Pharmaceutical Prevention of Influenza and ARVI «Antigripp» in Organized Children's Groups - I. B. Yakovlev; E. V. Sarmometov; I. V. Feldblum; I. I. Lvova (Детские инфекции (Москва))
The authors estimated epidemiological effectiveness of the program for prophylaxis of influenza and ARVI «Antigripp» for children of 7—12 years old. Children received Arbidol (capsules of 100 mg 2 times a week for 3 weeks) and Complivit activ. As a result there was a decline in absolute and relative indicators of ARVI morbidity risks. Epidemiological effectiveness of the program during the application of the drugs made up 56% and index of preventive efficacy was 2,3.